Profiling the Cytopathological Diagnosis of Enlarged Lymph Nodes on Fine Needle Aspiration Cytology - Shrestha, Sujan; Khadka, Dinesh; Bhandari Thapa, Anuja; Shrestha, Kshitiz (Journal of Nepal Health Research Council, 2022)
Background: This study aimed to assess the distribution of fine-needle-aspiration-cytology or biopsy findings through cytopathological patterns of lymph nodes aspirations in different age groups of the population visiting a tertiary level hospital in Kathmandu.Methods: The retrospective study was conducted on the database of the 226 lymphadenopathy cases that underwent biopsy fine needle aspiration cytology from 1 January 2016 to 31 December 2019 at the Department of pathology of Helping Hand’s Community Hospital, Kathmandu. A descriptive analysis was performed yielding proportions and counts for the quantitative variables. Chi-squared test was used to compare the proportions.  Point estimates and confidence intervals for measures of association were assessed with 95% confidence interval and p-value ?0.05 was considered statistically significant.Results: The 20-40 years were the most common age group undergoing biopsy fone needle aspiration cytology procedures. Males recorded majority of cases (68%, 153 of 226). The highest incidence of Reactive lymphadenitis was obtained (50%, 113 of 226) and it was the most common findings in the age group of <20 and 40-60 years. The Cervical lymph node (86%) was the most common anatomical location followed by axillary lymph nodes (8%). Squamous cell carcinoma and Adenocarcinoma accounted for more than half (53%, 20 of 38) of all the diagnosed malignancy. The incidence of Non-Hodgkin lymphoma and Hodgkin lymphoma were 8% (n = 3 of 38) and 5% (n = 2 of 38) respectively.Conclusions: Lymph node enlargement is associated with a wide range of etiologies with Reactive lymphadenitis as the most common cause and cervical lymph node as the common site.Keywords: Cytopathology; fine needle aspiration cytology; lymph node.